2020
DOI: 10.1097/spv.0000000000000869
|View full text |Cite
|
Sign up to set email alerts
|

#Urogyn: What’s Trending on Instagram? A Cross-sectional Observational Study

Abstract: Objective The aim of the study was to identify the prevalence, authorship, and type of information pertaining to topics in urogynecology on Instagram via hashtag and content analysis. Methods A list of 20 hashtags consisting of common urogynecologic diagnoses, procedures, and lay terms was derived from the American Urogynecologic Society’s “Patient Fact Sheets.” The top 9 and most recent 30 posts for each hashtag were reviewed for authorship and content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
3
8
0
Order By: Relevance
“…Our study aimed to further characterize the intended audience and content themes that emerged from physician-authored Instagram and Twitter posts compared with patients and AHP-authored posts using the official SGS urogynecology hashtags. The primary findings of this study are that physicians posted on Twitter more often than Instagram in contrast to patients who were more likely to post to Instagram and mirrors previously published findings 4 . However, both physician and patient-authored posts shared the most common thematic code, advocacy/awareness, indicating a common desire to raise awareness around the diagnosis and treatment of PFDs.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Our study aimed to further characterize the intended audience and content themes that emerged from physician-authored Instagram and Twitter posts compared with patients and AHP-authored posts using the official SGS urogynecology hashtags. The primary findings of this study are that physicians posted on Twitter more often than Instagram in contrast to patients who were more likely to post to Instagram and mirrors previously published findings 4 . However, both physician and patient-authored posts shared the most common thematic code, advocacy/awareness, indicating a common desire to raise awareness around the diagnosis and treatment of PFDs.…”
Section: Discussionsupporting
confidence: 79%
“…These algorithms are noted as an introduction of possible bias into post selection. Our post selection methodology was adapted from an Instagram study performed by Qin et al 4 in 2020 that searched Instagram’s “top 9” in addition to recent posts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in accordance with studies in other fields (dermatology, plastic surgery, and urogynecology) that have shown that the majority of top social media content is created by individuals without formal board-certified training. 10 , 13 , 14 , 25 …”
Section: Discussionmentioning
confidence: 99%